2020
DOI: 10.3390/jof6040219
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Beauveria bassiana from the Chagas Disease Vector Triatoma infestans in the Gran Chaco Region of Argentina: Assessment of Gene Expression during Host–Pathogen Interaction

Abstract: A native strain of the entomopathogenic fungus Beauveria bassiana (Bb-C001) was isolated from a naturally infected Triatoma infestans, Klug (Hemiptera: Reduviidae) adult cadaver in the Gran Chaco region, Salta province, Argentina. The isolate was both phenotypic and molecularly characterized in a context of fungus-insect interaction, by measuring the expression pattern of toxin genes during infection and immune response of T. infestans. The commercial strain GHA of B. bassiana, which was previously used in fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
(60 reference statements)
2
13
0
Order By: Relevance
“…Notably, a study in Triatoma infestans showed that, compared with the third day of infection, many of the antimicrobial peptide and defensin genes were significantly inhibited on the ninth day of infection (Mannino et al, 2019). Although the regulatory mechanism was not confirmed, it was largely due to fungal toxins (Baldiviezo et al, 2020). These findings suggest that fungi which secreted secondary metabolites can resist the immune system of the hosts at both genetic and non-physiological levels, which sets up the basis for toxin(s) pathogenicity.…”
Section: Fungal Toxins Versus the Insect Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, a study in Triatoma infestans showed that, compared with the third day of infection, many of the antimicrobial peptide and defensin genes were significantly inhibited on the ninth day of infection (Mannino et al, 2019). Although the regulatory mechanism was not confirmed, it was largely due to fungal toxins (Baldiviezo et al, 2020). These findings suggest that fungi which secreted secondary metabolites can resist the immune system of the hosts at both genetic and non-physiological levels, which sets up the basis for toxin(s) pathogenicity.…”
Section: Fungal Toxins Versus the Insect Immune Systemmentioning
confidence: 99%
“…Among these, Metarhizium anisopliae, Beauveria bassiana, and Bacillus thuringiensis are the most effective biological control agents against mosquito vectors (Montalva et al, 2016). Apart from B. thuringiensis, B. bassiana is the most commonly used biopesticide that can be effectively transmitted (Baldiviezo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In their natural environment, and especially during feeding, assassin bugs are exposed to various microorganisms. Insects can carry entomopathogens such as bacteria, fungi, and viruses [81,82] which could potentially affect and kill their predatory insects [83,84] via toxemia, bacteremia, or septicemia [85]. To analyze whether R. iracundus venom protects the assassin bug from potential pathogens, we tested its venom against Gram-positive and Gram-negative bacteria and found venom-mediated bacterial growth inhibition on Gram-negative E. coli only.…”
Section: Keeping the Glands Clean: The Antibacterial Activity Of Assassin Bug Venommentioning
confidence: 99%
“…EPF interplay host defence with factors which regulate adhesion to the cuticle, cuticle degradation, stress management and toxins [5]. Thus B. bassiana express bassianolide and beauvericin toxins during infection of the bug Triatoma infestans [6] and proteases, chitinases and lipase in the presence of C. suppressalis cuticle probably to pass the insects defence faster [1]. It was found that EPF peroxisome-type and hexagonal crystal-like organelles (Woronin bodies) are required for appressorium differentiation and the topical infection of insect hosts [7].…”
mentioning
confidence: 99%